The flowing of microplastics was accelerated under the influence of artificial flood generated by hydropower station. (10th May 2020) - Song, Jie; Hou, Chuanying; Zhou, Yang; Liu, Qi; Wu, Xuefei; Wang, Yuanjian; Yi, Yujun
Abstract: Rivers are considered the most important channel for microplastics traveling to the ocean from inland. The Yellow River is one of a main microplastics source for the Bohai Sea. As hydropower station operations—especially the artificial flood pulse—could significantly affect the transportation processes of microplastics, it is necessary to investigate the transportation regulation of microplastics from the Yellow River to the estuary. In this study, the distribution of microplastics (across 10 sections of the river from Xiaolangdi to the estuary) was detected at three stages (the pre-, inter-, and post-artificial flooding season). The result showed that the microplastic concentrations in the Yellow River ranged from 0.105 to 1.17 items m −2 . The main microplastic shapes found were foam and film, and the main components were expanded polystyrene and polyethylene. The average particle sizes were 1101.54, 484.93, and 509.46 μm at the three stages, respectively. The artificial flood accelerated the transport of microplastics from inland to the estuary and ocean; it also unified the overall particle size of microplastics along the river. The microplastics in the surface water of the study area likely originate mostly upstream of the Xiaolangdi Hydropower Station. The artificial flooding generated from water and sediment regulation transports a large amount of microplastics in the reservoirs and river channels to the estuary and offshore areas in a short time period via artificial flooding. Highlights: The artificial flood pulse accelerated the transport of microplastics from inland to the estuary and ocean. The flood pulse unified the overall particle size of microplastics along the river. The microplastics in the surface water of the lower Yellow River originate from the upstream reservoir. Compared to other main rivers worldwide, the overall concentration of microplastics of Yellow River was low.